CGIAR Research Program on Dryland Systems inception workshop for east and southern Africa - Quick comments from participants - International Livestock Research Institute (International Livestock Research Institute, 2012)
Quick comments from some of the participants in an east and southern Africa inception workshop for the CGIAR Research Program on Drylands. The meeting was held at the Nairobi headquaters of the International Livestock Research Institute (ILRI) 5-7 Jun 2011.